Off-label use of maraviroc in HIV-1-infected paediatric patients in clinical practice. (23rd October 2015) - Palladino, Claudia; Gómez, María Luisa Navarro; Soler-Palacín, Pere; González-Tomé, María Isabel; De Ory, Santiago J.; Espiau, María; Hoyos, Santiago Pérez; León-Leal, Juan Antonio; Méndez, María; Moreno-Pérez, David; Guasch, Claudia Fortuny; Sierra, Antoni Mur; et al.
Abstract : Maraviroc (MVC) is not approved for HIV-1-infected paediatric patients. This is the first assessment of the use of MVC-based salvage therapy in vertically HIV-1-infected paediatric patients in clinical settings. The results suggest that MVC-based salvage therapy is useful in children and adolescents with extensive resistance profile leading to maintained virological suppression in up to 88% of the patients with CCR5-tropic virus. The likelihood of treatment success might increase when MVC is combined with other active drugs. Abstract : Supplemental Digital Content is available in the text